1999
DOI: 10.1007/s004390050971
|View full text |Cite
|
Sign up to set email alerts
|

A high degree of aneuploidy in frozen-thawed human preimplantation embryos

Abstract: We have studied the chromosomal content in 68 normally fertilised freeze-thawed human embryos of good morphology from 34 patients with an average maternal age of 32,6 years. Forty embryos showed post-thaw cellular division and twenty-eight post-thaw cleavage arrest. After spreading of the embryos on microscope slides, analysis of chromosomes X, Y, 15, 16, 17 and 18 was performed using two rounds of fluorescent in situ hybridisation (FISH). According to the results, the embryos were divided into four groups: (I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
37
1
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(43 citation statements)
references
References 37 publications
(37 reference statements)
4
37
1
1
Order By: Relevance
“…In addition, there was an MSC with high aneuploidy levels and loss of mitotic activity after cryopreservation. Considering that previous studies reported an increase in aneuploidy levels in ESCs after cryopreservation [42,43], we speculated that this MSC with high aneuploidy levels was damaged during storage or freezing and thawing and was senescent without mitotic activity when thawed for re-culture. The chromosomal abnormalities of this MSC can only be detected by interphase FISH analysis, and thus karyotyping was impossible.…”
Section: Discussionmentioning
confidence: 92%
“…In addition, there was an MSC with high aneuploidy levels and loss of mitotic activity after cryopreservation. Considering that previous studies reported an increase in aneuploidy levels in ESCs after cryopreservation [42,43], we speculated that this MSC with high aneuploidy levels was damaged during storage or freezing and thawing and was senescent without mitotic activity when thawed for re-culture. The chromosomal abnormalities of this MSC can only be detected by interphase FISH analysis, and thus karyotyping was impossible.…”
Section: Discussionmentioning
confidence: 92%
“…Our data shows that 16.5% of the frozen embryos were normal. This difference could be attributed to the number of chromosomes observed, Iwarsson and colleagues [16] utilized 5 probe FISH while we performed 9 or 12 probe FISH. We did not standardize based on either 9 probe or 12 probe FISH because it would decrease our numbers.…”
Section: Discussionmentioning
confidence: 96%
“…Iwarsson and colleagues [16] found a high degree of chromosomal abnormalities in frozen-thawed embryos (25% normal). Our data shows that 16.5% of the frozen embryos were normal.…”
Section: Discussionmentioning
confidence: 99%
“…Mosaicism may be a reason for the lack of pregnancy success. Apparently, most normal embryos with good morphology contain one or more chromosomally abnormal blastomeres [34][35][36]. Firstly, apoptosis in one cell line is not necessarily lethal for the embryo if a chromosomally normal core persists.…”
Section: Discussionmentioning
confidence: 99%